Worldfish in India - Panemangalore, Arun (WorldFish, 2023)
Undernutrition is one of India’s most serious development challenges, with a particularly high burden of malnutrition among children. Small indigenous fish—which are rich in micronutrients—are often missing from diets in low-income communities. Small-scale fish producers could be part of the solution but they face suboptimal production outcomes with limited access to aquatic food production technologies and knowledge. Meanwhile, species diversity is declining due to habitat degradation and overexploitation of inland fisheries, exacerbated by climate change, which continues to threaten aquaculture.